(untitled) - Fagan, Brian (New York, 1995)
Today's archeologists are not treasure hunters but time detectives, utilizing advanced technology to vividly reconstruct the past from minute clues. With the focus in archeology shifting from the recovery of artifacts and antiquities to learning more about how our ancestors lived, archeologists now work in different ways. Frequently they are part of multidisciplinary teams of scientists who, for example, can reconstruct ancient diets from examination of bone collagen remains or describe millennia-old landscapes from fossilized seeds and grains. These new techniques enable us not only to better understand our past, but to better preserve it - excavations today move less earth in two years than those a couple of generations ago moved in a month. Time Detectives takes us around the world and through more than 15,000 years of human history as we visit the sites of some of the most breathtaking and significant finds of recent years.
Keywords: Khảo cổ học,Archaeology; Lịch sử,History